Criminalidad: jerarquía y poder de los reos sentenciados por homicidio calificado del penal el milagro 2005 - 2012 - Rodriguez Fernandez, Erick Constante (2014)
Peruvian prison situation, despite sorne efforts, continues to face a serious crisis. In general , the Peruvian prison is characterized as all prisons in the region to be populated by poor people and the different values which are commonly considered as positive, remains the physical and 1 or psychological violence; where everyday acts of corruption and abuse of power are evident not only between the authorities and the inmates, but also between those detainees and the State generates economic costs by keeping inmates in prisons, where the daily maintenance of an inmate is S 1. 4.00 in which includes breakfast, lunch and dinner, which multiplied by the total amount of a prison population (such as criminal Miracle, about 2500 inmates) being exorbitant amounts invested in them without any benefit to the S tate Peruano. The difference shows in the same prison where not so long ago the codes of honor honored without discussion in the underworld of crime. An old nest remained among inmates witho1:1t hesitation respecting the so-called" Taita", which in practice had a higher rank than himself appointed as Chief Interna! Pavilion which was under his control . In this sub - world and after " Taita", the top of the hierarchy were the assailants with the rank of " gang leaders " and drug traffickers, highlighting the top the most heartless, the prontuariados, which had more cuts in chest and arms. Secondly murderers, thieves, fraudsters and, last but deep down, sex offenders ( rapists ) .